Oral health situation analysis and integration of Massive Open Online Course Modules on Oral Health Promotion in WHO SEAR Countries: A Comprehensive Report - Ritu Duggal; Vijay Mathur; Harsh Priya; Bharathi M Purohit; Shalini Gupta; Deepika Mishra; Manali Deb Barma; Sneha Malhotra; Upendra S Bhadauria; Deepali Agarwal (National Board of Examinations Journal of Medical Sciences, 2024)
Background: Massive Open Online Course (MOOC) modules are deemed to be novel educational models to optimize learning. They can be useful in delivering oral health education to primary health care workers to strengthen the oral health care delivery system. Therefore, the aim of this study is to analyze the current oral health situation analysis of the South East Asia region countries and to assess areas where the MOOC modules can be integrated as oral health training material. Methodology: A focus group discussion was held virtually with 70 participants from SEAR. The MOOC modules were developed as learning activities to facilitate the application of the material learned, in public settings. The themes for the situation analysis were based on oral health policy, barriers to dental treatment needs and action plan for implementation of the MOOC modules in each SEAR country. Results: Results highlighted the importance of formulating and implementing oral health policy at the national level among the participating countries. Nepal, Maldives, Timor–Leste reported on existing gaps regarding the unmet dental treatment needs. The inclusion of helath care workers in conducting dental procedures was observed in Bhutan. Global school health promoting initiatives were recorded in Maldives. The participating SEAR countries reported on the sensitization of primary healthcare workers through the developed MOOC modules. Conclusion: The developed massive open online course module was acknowledged to be an improved and interactive tool for primary health care workers by the country's oral health officers for oral health promotion and networking.